Construction of High Ethanol Fermenting Halotolerant Hybrid by Intergeneric Protoplast Fusion of Saccharomyces cerevisiae and Zygosaccharomyces rouxii - Limtong, Savitree; Deejing, Somkid; Yongmanitchai, Wichien; Santisopasri, Wilia (Agriculture and Natural Resources, 1998)
Saccharomyces cerevisiae M30, a high ethanol producing flocculent strain, was hybridized with Zygosaccharomyces rouxii TISTR1750, a halotolerant non-flocculent strain, by polyethylene glycol induced protoplast fusion. The protoplast fusion of these two yeast genera occurred with frequency of 5.89X10-5. Three fusants, namely RM11, RM37 and RM58, were selected based on their high ethanol fermentation efficiency in glucose broth containing 1.5 and 3% sodium chloride. Ethanol fermentation performance in salted medium of the three fusants revealed that in glucose broth containing 1.5, 3, 5 and 7% sodium chloride RM11 produced the highest ethanol concentrations and yields when compared to the other two fusants and both parental strains. Ethanol production in semisynthetic medium consisted of 18% glucose and 3% sodium chloride in 5 l fermentor with controlling of pH not to be lower than pH 4.5, temperature at 30 C and 300 rpm agitation speed also showed that the efficiency of ethanol production of the fusant RM11 was the highest comparing with both parental strains. It revealed maximal ethanol as 6.85% by weight with 87% of theoretical yield at 60 h of cultivation. S. cerevisiae M30 produced ethanol 6.5% by weight with 83% of theoretical yield, while Zygosac. rouxii TISTR1750 produced 6.36% by weight with 79% of theoretical yield at the same cultivation period. The fusant RM11 exhibited flocculation the same as that of S. cerevisiae M30.